(untitled) (FAVE Sección Ciencias Veterinarias, 2016)
Growth is a key determinant of fitness in animals, and may be affected by the environmental challenges presented over the course of an individual’s lifespan. When faced with limited resources and environmental challenges, organisms may prioritize the development and maintenance of particular processes over others. To expand our understanding of the consequences of organism exposure to a changing environment, we offer a long-term experiment to compare the growth patterns of young male rats exposed and not exposed to food limitation and social conflict. The patterns of growth of young rats were altered by the exposure to these environmental challenges, two of the most frequently faced by animals. As expected, scarcity of food resulted in a marked growth decline in animals exposed to nutritional stress. Interestingly, individuals exposed to an unstable social environment, but fed ad libitum, evidenced a growth rate 6% smaller than those under stable social conditions. An interaction between food limitation and social conflict was not observed. As a larger body size growth results in a competitive advantage in encounters, the detected divergence on growth patterns may represent significant consequences on the individual’s life trajectory.